2020
DOI: 10.1088/1361-6455/ab91e3
|View full text |Cite
|
Sign up to set email alerts
|

Normal density and moment of inertia of a moving superfluid

Abstract: In this work, the normal density ρn and moment of inertia of a moving superfluid are investigated. We find that, even at zero temperature, there exists a finite normal density for the moving superfluid. When the velocity of superfluid reaches sound velocity, the normal density becomes total mass density ρ, which indicates that the system losses superfluidity. At the same time, the Landau’s critical velocity also becomes zero. The existence of the non-zero normal density is attributed to the coupling between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A future direction would be to consider the extension of these ideas to superfluidity of the stripe phase of a spin-orbit coupled BEC (see [52][53][54][55]), in which Galilean invariance is also broken. It might also be necessary to explore scenarios in which the supersolid state may not necessarily be the ground state, but rather exhibits specific excitations of its phase profile [56] (also see [57]) or lattice distortions. In the latter case, our results already suggest this will lead to anisotropic effects in the superfluid response.…”
Section: Discussionmentioning
confidence: 99%
“…A future direction would be to consider the extension of these ideas to superfluidity of the stripe phase of a spin-orbit coupled BEC (see [52][53][54][55]), in which Galilean invariance is also broken. It might also be necessary to explore scenarios in which the supersolid state may not necessarily be the ground state, but rather exhibits specific excitations of its phase profile [56] (also see [57]) or lattice distortions. In the latter case, our results already suggest this will lead to anisotropic effects in the superfluid response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is found that, there exist only one gapless excitation near q = 0, which corresponds to total density oscillations. The superfluid density can be also calculated with current-current correlation [10,32,48] or phase twist method [49,50]. Assuming the superfluid order parameters undergo a phase variation, e.g, △ i → ∆ i e 2iq•ri , The superfluid density (particle number per unit cell) tensor ρ sij can be written as…”
Section: An Example: Superfluid Density In Haldane-hubbard Modelmentioning
confidence: 99%
“…In addition, it is found that, there exists only one gapless excitation near , which corresponds to total density oscillations. The superfluid density can be also calculated with current–current correlation functions 9 , 34 , 47 or phase twist method 46 , 60 . Assuming the superfluid order parameters undergo a phase variation, e.g, , the superfluid density (particle number per unit cell) tensor can be written as where is thermodynamical potential (per unit cell) in grand canonical ensemble.…”
Section: Introductionmentioning
confidence: 99%